PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SESUAI AJARAN ISLAM SISWA KELAS V MI MAARIF DUKUH - Peni Nur Hidayati (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2019)
This study aims to determine clean and healthy behavior (PHBS) that is in accordance with Islamic teachings. This study uses a qualitative research method with triangulation (combined) data collection techniques. The validity test of the data in this study used data triangulation techniques. The results of this study basically students have applied PHBS in schools, for example: maintaining cleanliness of clothing and body, habit of washing hands, disposing of garbage in place, regular exercise, snacks in a healthy school canteen, and so forth. However, these habits have no direct mentoring or supervision by the teacher. This makes students still do not wash their hands, some even wash their hands just by soaking their hands without rubbing the entire hand and between fingers until clean using soap. In addition, teachers and UKS officers forget to provide clean soap and towels beside the hand washing place. In removing garbage in its place some students can do it correctly, but due to lack of supervision, there are still students who throw litter. From this study it can be concluded that MI Maarif Dukuh has conducted PHBS health education in accordance with Islamic teachings in the school environment. Students of MI Maarif Dukuh have a clean and healthy lifestyle. This can be seen from the hand washing routines carried out by students before and after meals, as well as after sports activities. All teachers and employees view the importance of PHBS education and health education for all MI students, but this study is more focused on class V students.